1999
DOI: 10.1128/jvi.73.6.4561-4566.1999
|View full text |Cite
|
Sign up to set email alerts
|

Redox and Activation Status of Monocytes from Human Immunodeficiency Virus-Infected Patients: Relationship with Viral Load

Abstract: Monocytes are precursors of tissue macrophages, which are major targets of human immunodeficiency virus type 1 (HIV-1) infection. Although few blood monocytes are infected, their resulting activation could play a key role in the pathogenesis of HIV disease by modulating their transendothelial migration and inducing the production of reactive oxygen species (ROS). ROS participate in chronic inflammation, HIV replication, and the apoptosis of immune system cells seen in HIV-infected subjects. Published data on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 45 publications
5
42
1
3
Order By: Relevance
“…PWH have high reactive species production in peripheral immune cells (67,68) and elevated lipid peroxidation products in plasma (69). We and others have previously shown that RBCs are especially susceptible to oxidative damage by lipid peroxidation (32,33,70), resulting in release of hemoglobin (Hb), metHb, free heme, and free iron (71).…”
Section: Discussionmentioning
confidence: 99%
“…PWH have high reactive species production in peripheral immune cells (67,68) and elevated lipid peroxidation products in plasma (69). We and others have previously shown that RBCs are especially susceptible to oxidative damage by lipid peroxidation (32,33,70), resulting in release of hemoglobin (Hb), metHb, free heme, and free iron (71).…”
Section: Discussionmentioning
confidence: 99%
“…HIV patients have a depletion of glutathione in plasma, lymphocytes and monocytes (165) along with reduced levels of SOD (166). At the same time, monocytes from HIV patients have increased ROS production, which correlated with viral load (167). HIV induces oxidative stress, with a number of its proteins (Tat, gp41, Vpr) involved in deregulating different pathways to increase ROS production (168).…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%
“…14 Rather than being deleterious to HIV, free radical activity has been shown to be a prominent host factor in the activation of virus from the latent state and for increased virus replication. 3,15 Reverse transcriptase therefore plays an integral role in HIV replication and could not have evolved specifically as an evasion strategy. Instead, it is through the lack of RT error correction activities that this mode of evasion has evolved and has indirectly, without HIV acquiring host genes, allowed this replicative mechanism to provide an immune evasion advantage.…”
Section: Evolution Of Evasion Strategies: An Rna Virus Examplementioning
confidence: 99%